ETNOMATEMATIKA DI PASAR KAMU SEBAGAI SUMBER PEMBELAJARAN MATEMATIKA - Minta Ito Simamora; Najwah Rokan (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2023)
Mathematics in essence grows from skills or activities of the cultural environment, so that a person's mathematics is influenced by his cultural background. Ethnomatematics is a complex and dynamic representation that describes the cultural influence of the use of mathematics in its application. From ethnomathematics researchers will research and analyze food and musical instruments in Pasar Kamuu. From food and musical instruments in Pasar Kamu to research from culture associated with mathematics. The food and musical instruments used by researchers were long endok food, ciwel cakes, dange cakes, putu bamboo cakes and musical instruments namely drum percussion, accordion, and barrel bonang. This study aims to analyze mathematics in food and musical instruments for learning mathematics and to find out the relationship between ethnomathematics and food and musical instruments in Pasar Kamu so that it can be used as a source of learning mathematics. This research is a type of descriptive research that uses a qualitative research approach methodology. Based on the results of the assistance and coding that has been carried out by the researchers, it is known that there is an ethnomathematics connection with food and musical instruments at Pasar Kamu Market so that it can be used as a source of learning mathematics in the material, namely: a. Area and Circumference of Flat Shape, b. Space Build Volume